Double sequential external defibrillation versus standard defibrillation in refractory ventricular fibrillation: A systematic review and meta-analysis - Li, Yongkai; He, Xiaojing; Li, Zhuanyun; Li, Dandan; Yuan, Xin; Yang, Jianzhong (Frontiers in Cardiovascular Medicine, 2022)
Introduction Double sequential external defibrillation (DSED) in cardiopulmonary resuscitation has shown different results in comparison with standard defibrillation in the treatment of refractory ventricular fibrillation (RVF). This review aims to compare the advantages of DSED with standard defibrillation in the treatment of refractory ventricular fibrillation. Materials and methods PubMed, Embase, Web of Science, and Cochrane Library were searched from inception to May 1, 2022. Studies included adult patients who developed RVF. The study used random-effects and fixed-effects models for meta-analysis, which was reported by risk ratio (RR) with 95% confidence interval (CI), mean difference (MD), or standardized mean difference (SMD). The risk of bias in individual studies was assessed using the Robins-I tool for observational studies and the Cochrane Risk of Bias 2 (ROB-2) tool for clinical trials. Primary outcomes included the termination of RVF, prehospital return of spontaneous circulation (ROSC), survival to hospital admission, survival to hospital discharge, and good neurological recovery. Secondary outcomes included age, total defibrillation attempts, emergency medical system arrival time, and dose of epinephrine and amiodarone used. Results In this systematic review and meta-analysis, 10 studies containing 1347 patients with available data on treatment outcomes were included. The pooled estimate was (RR 1.03, 95% CI, 0.89 to 1.19; Z = 0.42, P = 0.678 > 0.05) for Termination of RVF, (RR 0.84, 95% CI, 0.63 to 1.11; Z = 1.23, P = 0.219 > 0.05) for ROSC, (RR 0.86, 95% CI, 0.69 to 1.06; Z = 1.4, P = 0.162 > 0.05) for survival to hospital admission, (RR 0.77, 95%CI, 0.52 to 1.15; Z = 1.26, P = 0.206 > 0.05) for survival to hospital discharge, (RR 0.65, 95%CI, 0.35 to 1.22; Z = 1.33, P = 0.184 > 0.05) for good neurologic recovery, (MD −1.01, 95%CI, −3.07 to 1.06; Z = 0.96, P = 0.34 > 0.05) for age, (MD 2.27, 95%CI, 1.80 to 2.73; Z = 9.50, P = 0.001 < 0.05) for total defibrillation attempts, (MD 1.10, 95%CI, −0.45 to 66; Z = 1.39, P = 0.16 > 0.05) for emergency medical system arrival time, (SMD 0.34, 95%CI, 0.17 to 0.50; Z = 4.04, P = 0.001 < 0.05) for epinephrine, and (SMD −0.30, 95%CI, −0.65 to −0.05; Z = 1.66, P = 0.1 > 0.05) for amiodarone. Conclusion We discovered no differences between DSED and standard defibrillation in termination of RVF, prehospital return of spontaneous circulation, survival to hospital admission, survival to hospital discharge, good neurological outcome, emergency medical system arrival time, and amiodarone doses in patients with RVF. There were some differences in the number of defibrillations and epinephrine doses utilized during resuscitation. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=329354], identifier [CRD42022329354].